A Brief History of Metacognitive Therapy: From Cognitive Science to Clinical Practice. Issue 1 (February 2023) - Capobianco, Lora; Nordahl, Henrik
Highlights: Metacognitive therapy (MCT) is an effective treatment for anxiety and depression. In this article we trace the historical development of MCT. We explain why the metacognitive approach has developed into a promising perspective. We argue that MCT may mark a paradigm shift in psychotherapy. Its development may serve as a blueprint for advancement in clinical psychology. Abstract: Metacognitive therapy (MCT) is proving to be an effective treatment for anxiety and depression with effects that may exceed CBT. It has been described as a paradigm shift in psychotherapy in its theory-driven cognitive science approach and systematic development and evaluation. MCT was developed by Adrian Wells based on an information processing theory, the Self-Regulatory Executive Function model by Wells and Matthews. MCT theory formulates psychological disorders as sharing common causal factors under the influence of metacognition, representing a particular top-down model of biases in cognitive regulation. A key clinical implication was that a core set of interventions could be developed to impact a wide range of symptoms and disorders. In this paper, we trace the historical development of MCT and the major studies that informed theory and practice with the aim of introducing clinicians and researchers to this area and to understand why the metacognitive approach has developed into a treatment that is proving to be potentially more effective than current gold-standard treatments. In doing so, we will draw out the distinctive features of the approach and explore how this might offer a blueprint for scientific advancement in clinical psychology and psychotherapy.